A Review of Biomaterials and Their Applications in Drug Delivery - Reza Rezaie, Hamid; Esnaashary, Mohammadhossein; Aref arjmand, Abolfazl; Öchsner, Andreas (SpringerBriefs in Applied Sciences and Technology, 2018)
This book reviews drug delivery systems as mechanisms to introduce therapeutic agents into the body to help or improve tissue function, and examines different drug delivery systems applied in various organs. To date, polymeric systems, ceramic particles or composites have been used in different applications such as injectable, coatings of implants, scaffolds, or implantable devices. Such systems should be able to retain the therapeutic agent and release it in uniform amounts at a specific time.